2002
DOI: 10.30972/agr.09470
|View full text |Cite
|
Sign up to set email alerts
|

Importancia de la calidad de la miel

Abstract: La miel es la sustancia dulce producida por las abejas obreras a partir del néctar de las flores o dela exudación de otras partes vivas de las flores presentes en ellas, que dichas abejas recogen, transforman y combinan con sustancias específicas, y almacenan después en panales. La miel es un producto natural ideal para la alimentación, porque en su composición química existen azúcares simples como la glucosa (40%) y fructosa (35%), que no necesitan transformación por los jugos gástricos para ser digeridos. Un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 2 publications
(2 reference statements)
0
2
0
1
Order By: Relevance
“…Our results showed that consumers with high agreement level towards the SFSC exhibited higher WTP for some local honey and lower WTP for non-local one both before and after the hedonic evaluation. However, this tendency was related to the global acceptability and the Subovsky et al (2002), which strengthens the idea of making greater efforts for the development of local markets of local produced honeys that highlight their own attributes in each region. The richness of floral biodiversity and the special climatic conditions of the producing region in Mar de Plata plays a key factor in promoting the expansion of the apiculture activities (Subovsky et al, 2002).…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Our results showed that consumers with high agreement level towards the SFSC exhibited higher WTP for some local honey and lower WTP for non-local one both before and after the hedonic evaluation. However, this tendency was related to the global acceptability and the Subovsky et al (2002), which strengthens the idea of making greater efforts for the development of local markets of local produced honeys that highlight their own attributes in each region. The richness of floral biodiversity and the special climatic conditions of the producing region in Mar de Plata plays a key factor in promoting the expansion of the apiculture activities (Subovsky et al, 2002).…”
Section: Discussionmentioning
confidence: 74%
“…However, this tendency was related to the global acceptability and the Subovsky et al (2002), which strengthens the idea of making greater efforts for the development of local markets of local produced honeys that highlight their own attributes in each region. The richness of floral biodiversity and the special climatic conditions of the producing region in Mar de Plata plays a key factor in promoting the expansion of the apiculture activities (Subovsky et al, 2002). This represents a challenge and great potential for the diversification, differentiation and added value to the territorial apicultural production.…”
Section: Discussionmentioning
confidence: 74%
“…Por el origen botánico está la miel de flores proveniente del néctar de las flores, monoflorales y poliflorales y la miel de mieladas de la exudación de las partes vivas de las plantas o presentes en ellas. Por su elaboración se clasifican en miel de panal, que es la depositada por las abejas en panales de reciente construcción y sin larvas; miel centrifugada obtenida mediante centrifugación de los panales desoperculados, sin larvas y, la miel prensada, obtenida de la compresión de los panales, sin larvas, con o sin aplicación de calor moderado (Subovsky, M., Castillo, A., Sosa, Á. & Cano, N., 2002).…”
Section: Introductionunclassified